Characterisation of a ssDNA aptamer with inhibitory activity on interaction between SARS-COV-2 spike 1 protein and human ACE2 protein as a potential treatment for Covid-19 - Zi Yuan Chang; Falah Abbas Muhamad Salih Alhamami; Kai Ling Chin (Penerbit UPM, 2025)
Introduction: In late 2019, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged, rapidly evolving and causing the ongoing coronavirus disease 2019 (Covid-19). Current antiviral treatments for Covid-19 are expensive and often lead to adverse side effects, necessitating the discovery of a new treatment strategy. All SARS-CoV-2 variants utilise the spike 1 (S1) protein to bind to human cells via the angiotensin-converting enzyme 2 (ACE2) receptor, making disruption of this S1-ACE2 interaction using ACE2-targeting aptamer a promising Covid-19 treatment strategy. Materials and methods: ACE2-targeting single-stranded deoxyribonucleic acid (ssDNA) aptamers were isolated using magnetic bead-based systematic evolution of ligands by exponential enrichment (SELEX) meth- od. The isolated aptamers were predicted for their structure and interaction with ACE2 using in-silico analysis. Those aptamers bound to the ACE2 site recognised by the S1 were evaluated for binding properties by quantitative poly- merase chain reaction (qPCR). Subsequently, the aptamer demonstrating specificity and the highest affinity toward ACE2 was further assessed for its inhibitory potential on the S1-ACE2 interaction using a competitive-based ELISA approach. Results: Seventeen aptamers were successfully isolated with seven of them binding to the site recognised by the S1 protein. One of the aptamers, Apt 17, exhibited binding specificity to ACE2 and showed the highest binding affinity with a dissociation constant (Kd) of 64.53 ± 18.39 nM. This aptamer effectively inhibits the S1-ACE2 inter- action (p<0.01). Conclusion: Apt 17 serves as a promising therapeutic candidate for future Covid-19 therapy or for addressing emerging diseases mediated by viruses utilising ACE2 for cell entry.